THE EFFECT OF BROMELAIN ENZYME CONCENTRATION ON THE DEGREE OF HYDROLYSIS OF EEL PROTEIN HYDROLYZATE (Monopterus albus) - Mhd. Taufik Harahap; Edison Edison; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTProtein hydrolyzate is a product resulting from the decomposition of fish protein into short chain compounds. The bromelain enzyme used in the hydrolysis process of protein hydrolyzate affects the value of the degree of hydrolysis. Enzyme concentration can determine the degree of hydrolysis produced. This study aimed to determine the best bromelain enzyme concentration in producing the degree of hydrolysis of eel protein hydrolyzate. The method used in this study was an experimental method using a non-factorial completely randomized design. The treatment consisted of 3 levels, namely 5% bromelain enzyme concentration (B1), 6% bromelain enzyme (B2), and 7% bromelain enzyme (B3) with a hydrolysis time of 5 hours. Parameters analyzed were degree of hydrolysis and yield. The results obtained that the bromelain enzyme concentration affected the degree of hydrolysis and yield. 7% bromelain enzyme concentration was the optimum condition for protein hydrolysis with hydrolysis degree of 6.46 and yield of 10.52%. Keywords: Bromelain, hydrolyzate, hydrolysis, Monopterus albus